Prevalence and risk factors profile of seropositive Toxoplasmosis gondii infection among apparently immunocompetent Sudanese women - Mustafa, Madinna; Fathy, Fatima; Mirghani, Abubaker; Mohamed, Mona A.; Muneer, Mohamed S.; Ahmed, Abdallah E.; Ali, Mohamed Siralkhatim; Omer, Rihab A.; Siddig, Emmanuel E.; Mohamed, Nouh S.; Abd Elkareem, Amjed M. (BMC research notes, 2019)
Objectives Toxoplasma gondii is an opportunistic parasite that causes a clinical manifestation known as toxoplasmosis. We investigated the prevalence and potential risk factors of T. gondii infection among women in Khartoum, Sudan. A sero-parasitological cross-sectional study included 100 women aging between 15 and 50 years old was conducted between January and November 2018. Serum samples were collected and investigated for the presence of anti- T. gondii immunoglobulins. Results Mean age of the women population included was 26.75 ± 8.25 with a range between 15 and 50 years. Sero-prevalence of T. gondii antibodies was 27% (27/100) with a 95% confidence interval (CI) of 18.6–36.8%. Among seropositive population 81% (22/27), 15% (4/27) and 4% (1/27) were seropositive for IgG antibodies, IgM antibodies and both antibodies respectively. Age group 21–30 years old had the highest frequency of detected IgG (10/45) and IgM (3/45). Married women had the highest frequency of detected IgG or IgM, 18/79 and 3/79, respectively. Risk factors analysis showed a total of 37/100 participants were having direct contact with cats and 66/100 have a frequent raw meat consumption, neither direct cats contact nor raw meat consumption had a statistically significant association with seropositivity to T. gondii (P value = 0.052 and 0.565, respectively).